Benefits of home-based stimulation versus institutional intervention of speech and language on spectrum of children with autism during COVID-19 lockdown - Chatterjee, Nikita; Bose, Ambika; Singh, Robin; Kumar, Suman (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: The study aims to evaluate and compare the effectiveness of home-based stimulation and institution-based speech and language interventions in children with autism spectrum disorder (ASD). Methods: An exploratory study was conducted on 26 children aged 2.5 to 5 years (mean age: 3.39 years, SD±0.47) with communication difficulties. The participants were divided into two groups: Group I (n=12) received home-based stimulation administered by caregivers, with monthly professional monitoring and guidance. Group II (n=14) received institution-based intervention, attending sessions twice weekly. Post-intervention evaluations were conducted after three months. Results: Both groups demonstrated significant improvements in receptive language (p<0.05), with higher scores observed in Group II, particularly in children with traits or mild autism, followed by moderate autism. Expressive language skills showed significant pre- and post-intervention improvements in both groups (p<0.05). Attention skills improved significantly within and between groups (p<0.05). Social and cognitive skills also improved significantly in both groups, although group II exhibited better social and cognitive improvements overall. In contrast, group-I showed stronger gains in cognitive skills compared to social skills. Conclusions: Both home-based and institution-based interventions positively impacted children with autism. However, a combination of these approaches yielded the most substantial benefits for the children’s developmental outcomes and contributed positively to the mental health of their caregivers.